2010
DOI: 10.1037/a0017519
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sources of competence underlying the comprehension of inconsistencies: A developmental investigation.

Abstract: How do children know the sentence "the glass is empty and not empty" is inconsistent? One possibility is that they are sensitive to the formal structure of the sentences and know that a proposition and its negation cannot be jointly true. Alternatively, they could represent the 2 state of affairs referred to and realize that these are incommensurate, that is, that a glass cannot simultaneously be empty and contain something. In 2 studies, the authors investigated how children (N = 186; ages 4-8) acquire compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…"), 6-year-olds successfully identified the pair of statements that did not "make sense." Morris and Hasson (2010) found that children demonstrated the ability to determine whether two states were at odds (e.g., "There is a sticker in the box." and "The box is empty.")…”
Section: Children's Treatment Of Inconsistent Illogical and Improbamentioning
confidence: 98%
“…"), 6-year-olds successfully identified the pair of statements that did not "make sense." Morris and Hasson (2010) found that children demonstrated the ability to determine whether two states were at odds (e.g., "There is a sticker in the box." and "The box is empty.")…”
Section: Children's Treatment Of Inconsistent Illogical and Improbamentioning
confidence: 98%
“…As noted earlier, very little research has examined children’s ability to recognize weak explanations presented individually. Past research has found that by age 6 or 7, children can detect logical inconsistencies in very simple individual claims (e.g., that a glass cannot be full and empty at the same time; Morris & Hasson, 2010 ; Ruffman, 1999 ). There is also evidence that preschool-aged children appear less satisfied when their questions are addressed with nonexplanatory responses that are not actually answers (e.g., restating the question, providing a personal reaction) than with real explanations (Frazier, Gelman, & Wellman, 2009 ), and that they show better recall for causal explanations (Frazier, Gelman, & Wellman, in press ).…”
mentioning
confidence: 99%
“…As far as we can see, assuming that contradictions are not all alike is the only way to allow for simple inferences out of premises containing contradictions, while being consistent with making ex falso a difficult inference pattern to accept. A further empirical reason to distinguish different contradictions representationally is that naïve reasoners most likely do not realize automatically when they are entertaining contradictions (Morris and Hasson, ).…”
Section: A Bird's‐eye View Of the Theorymentioning
confidence: 99%
“…If our successes of reasoning are as much a part of the explananda as our failures, as we argued in section , then the erotetic theory needs a way to eliminate contradictory alternatives from mental models. Although naïve reasoners most likely do not realize automatically when they are entertaining contradictions (Morris and Hasson, ), we take it that a reasoner can go over the mental model in discourse and filter out each contradictory molecule, incurring a processing cost. We call this the Filter operation, and in addition it eliminates double negations from particular atoms such as ¬¬p.…”
Section: The Core Fragmentmentioning
confidence: 99%